P297 Treatment of patients with complex perianal Crohn's disease with darvadstrocel: a single-institution real life experience. (21st January 2022) - Borruel PhD, N; Martí, M; Armario, D; Ibarz, A; Robles, V; Herrera, C; Mayorga, L; Pérez, Z; Alonso, C; Elena, C; Planes, M; Oller, E; et al.
Abstract: Background: Complex perianal disease in patients with Crohn's disease (CD) represents a therapeutic challenge since, despite biological treatment, half of the patients do not achieve an adequate response. Treatment with allogenic expanded adipose-derived mesenchymal stem cells (Darvadstrocel) has proven to be an innovative treatment in patients refractory to treatment with immunomodulators and anti-TNF antibodies. Methods: To assess the efficacy of Darvadstrocel treatment in clinical practice in patients with CD and complex perianal fistula. Method : We performed a prospective descriptive study in patients with CD and complex perianal fistula (high intersphincteric, transsphincteric, extrasphincteric or suprasphincteric; presence or ≥ 2 external opening or abscesses), refractory to antiTNF treatment, treated consecutively with Darvadstrocel at our Crohn's and Colitis Attention Unit. Each patient was treated with 120 million stem cells (half of the dose was injected along the tract walls and the other half around the internal opening/s). Response to treatment was assessed as combined remission according to the criteria of the ADMIRE study (clinical assessment of closure of all treated external openings that drained before treatment and absence of collections> 2 cm confirmed by MRI). Results: From July 2020 to October 2021 12 patients (10M / 2H) have been treated with Darvadstrocel. All patients were in clinical remission (luminal disease) and had perianal disease refractory to anti-TNF treatment. In addition, 7/12 patients were also refractory to ustekinumab. The patients had previously been treated with a mean of 5.7 perianal surgeries (1–16), most of them curettage and seton placement or replacement. One patient had previously been treated with mesenchymal stem cells in 2014 (ADMIRE participant). All fistulas were complex, 5 with a single tract, 2 with a branched tract and 5 with a double tract; 7 were transsphincteric, 1 intersphincteric (double), 1 supraelevator, 1 suprasphincteric, and 2 extrasphincteric. 6/10 patients underwent a previous conditioning surgery (cleaning, curettage and seton placement) two weeks before cell administration. Six of the 10 patients with a follow-up of at least 6 months had combined remission (60%). Two of the three patients with a 1-year follow-up presented combined remission. Regarding safety, no relevant adverse effects have been observed: 2 patients presented abscesses in the immediate postoperative period (self-drained without subsequent recurrence). Conclusion: In real-life clinical practice, treatment with Darvadstrocel can be an effective and safe therapy in patients with CD and complex perianal disease refractory to biological treatment.